Problematika Guru Dalam Pengunaan Vidio Youtube Sebagai Media Pembelajaran di SMPN 1 Sidorejo - Rifqi Fadhillah Auliya; Rima Khusniati; Rizky Giar Fatnawa; Rista Riski Awwalin (Institut Agama Islam Sunan Giri Ponorogo, 2024)
The purpose of this research is to examine the problems of internal teachers using YouTube videos as learning media at SMPN 1 Sidorejo, so this research is important to do. This type of research is descriptive research with a qualitative approach. Collection method data using interviews, observation, and documentation with using research tools in the form of interview guides. Data obtained in research, it is researched descriptively by means of reduction, presentation, and drawing conclusions. The results of this research on problems that identified can be used as a reference for teachers to solve problems when using YouTube videos as a medium for learning and achieving higher quality learning. The limitations of this research are: teacher problems in the realm of junior high school learning at SMPN 1 Sidorejo.